Regulation of ovarian function by growth hormone: Potential intervention of ovarian aging - Han, Lei; Tian, Hongcheng; Guo, Xiaoxiao; Zhang, Lei (Frontiers in Endocrinology, 2023)
Growth hormone (GH) is mainly secreted by eosinophils of anterior pituitary gland. GH plays an important role in regulating the growth and development of many tissues and cells, so it is used in the treatment of many diseases. In recent years, the regulation of GH on ovarian function has attracted much attention. GH has been applied in controlled ovarian hyperstimulation, particularly in the patients with advanced age, diminished ovarian reserve (DOR) and poor ovarian response (POR). GH can directly bind to the growth hormone receptor (GHR) on the ovary to promote the growth, maturation and ovulation of follicles, as well as to inhibit follicular atresia. GH so as to promote the occurrence of early follicles, enhance the sensitivity of follicles to gonadotropins, accelerate the maturation of oocyte nucleus, improve mitochondrial activity and the quality of oocytes through the insulin-like growth factor (IGF) system, which is an indirect regulation. The deep-seated effects of GH on human reproduction and ovarian aging need further basic research and clinical practice.